Long‐term incidence of vitrectomy and associated risk factors in young Danish patients with Type 1 diabetes: the Danish Cohort of Paediatric Diabetes 1987. Issue 4 (25th November 2014) - Broe, R.; Rasmussen, M. L.; Frydkjaer‐Olsen, U.; Olsen, B. S.; Mortensen, H. B.; Peto, T.; Grauslund, J.
Abstract: Aims: To examine the long‐term incidence of vitrectomy in young people with Type 1 diabetes. Methods: We prospectively studied 324 people with Type 1 diabetes who participated in baseline examinations in 1995. Surgical history was obtained from the Danish National Patient Registry in April 2012. Results: During the 17‐year study period, 39 people (12.0%) underwent vitrectomy at least once. The mean age and diabetes duration at first vitrectomy were 29.8 and 22.9 years, respectively, and 64.1% of the participants were men. In multivariable Cox regression analysis, baseline age (hazard ratio 0.81 per 1 year increase), BMI (hazard ratio 1.21 per 1 kg/m 2 increase), HbA1c (hazard ratio 1.72 per 1% increase) and diabetic retinopathy (hazard ratio 2.85 and 6.07 for mild and moderate/severe diabetic retinopathy vs none, respectively) were independent predictors of vitrectomy ( P  <   0.05 for all variables). Conclusions: Vitrectomy is a relatively common procedure in young people with Type 1 diabetes, with poor glycaemic control being the strongest modifiable risk factor. What's new?: Incidence rates of vitrectomy for people with diabetes are sparsely investigated, making it hard for clinicians to give adequate information at examinations. This is the longest prospective study to date to examine how frequently vitrectomy is needed in young people with Type 1 diabetes. In this population‐based cohort, 12% of people with Type 1 diabetes had vitrectomy performed during 17 years of follow‐up. The mean age at first surgery was < 30 years, with the strongest modifiable risk factor being glycaemic control. Clinicians should inform patients of this relatively high risk of needing surgery at a young age.